Changing Indications and Risk Factors for Peripartum Hysterectomy - Rubina Ashraf,Attiya Begum, Khansa Iqbal, Fehmida Shaheen (Journal of Rawalpindi Medical College, 2015)
Background: To determine the changing indications and risk factors for Peripartum Hysterectomy (PH), comparing the present times with the nineteen eighties. Methods: This retrospective comparative study was conducted in the Department of Obstetrics and Gynaecology (Unit-II) at Holy Family Hospital, Rawalpindi. Data of patients undergoing PH over a five-year period in the nineteen eighties, extending from June 1984 to May 1989 was collected. All ladies delivered during this period constituted Group A. The clinical record of all patients undergoing peripartum hysterectomy in the recent five-year period from January 2010 to December 2014 was examined to determine the indications and risk factors which necessitated this surgery. All women delivered in this time period constituted Group B. Peripartum Hysterectomy was defined as hysterectomy performed at the time of delivery or within the immediate postpartum period of 48 hours. All women of more than 28 weeks of gestation undergoing peripartum hysterectomy were enrolled. Results: The total number of deliveries conducted in Group A (1984-89) was 7843. Total vaginal deliveries were 6795(86.6%), while 1048(13.4%) were Caesarean sections(CS). In Group B (2010-14) total deliveries were 45340. Vaginal births were 29948(66%) and Lower Segment Caesarean section was performed in 15392(34%). In Group A, ten women required peripartum hysterectomy with a rate of 1.3/1000 deliveries Five of these (50%) were done for uterine rupture. Four (40%) were done for postpartum haemorrhage. One was done for placenta previa without previous caesarean section. One hundred and thirty six patients in Group B underwent peripartum hysterectomy with a rate of 2.9/1000 deliveries. In this group fifty-six (41%) were for postpartum haemorrhage, and forty-one (30.2%) for morbidly adherent placenta praevia on previous C-section scar (MAPCS). Uterine rupture led to peripartum hysterectomy in twenty (14.7%) cases. Conclusions: Uterine rupture was previously the leading indication for peripartum hysterectomy, followed by postpartum haemorrhage. With a rise in caesarean section rate, placenta praevia on previous scar and postpartum haemorrhage are now the leading risk factors for peripartum hysterectomy.